Adsorption of Pb and Cd in rice husk and their immobilization in porous glass‐ceramic structures. Issue 1 (9th September 2019) - Sharifikolouei, Elham; Baino, Francesco; Galletti, Camilla; Fino, Debora; Ferraris, Monica
Abstract: Rice husk, an agricultural waste, is abundantly available in many countries such as China, India, Brazil, US, and South East Asia. Despite the massive production of rice husk, it is mainly disposed to landfill. In this work, utilization of rice husk for a potential waste‐water treatment is evaluated, along with subsequent encapsulation of the adsorbed heavy metals (Pb and Cd) inside a porous glass‐ceramic. Vitrified bottom ash (another source of waste) was mixed with foaming agents in dif‐ ferent weight ratios (40:60, 50:50, and 60:40) to prepare a glass matrix for encapsulation of Pb‐/Cd‐loaded rice husk. It was shown that using 40 wt% vitrified bottom ash with 60 wt% foaming agents leads to a foam glass with the best pore size distribution. Therefore, this batch was further mixed with 70 volume% (5 wt%) heavy metal‐loaded rice husk and was heat‐treated at 750°C for 3 hours. The final glass‐ceramic porous structure was char acterized using SEM, XRD, compression test, and it was shown that it is safe to be used as it passes the EN12457‐2 leaching test.